THE EFFECTIVENESS OF VIDEO-ASSISTED PROBLEM-BASED LEARNING MODEL ON STUDENTS' SCIENCE LITERACY SKILLS OF VIBRATION AND WAVE MATERIAL IN SMP NEGERI 27 MEDAN. - Sembiring, Surya Karinanta; Hardinata, Aristo (Department of Science Education, 2024)
This study aims to determine the effectiveness of the video-assisted PBL learning model on students' science literacy skills on vibration and wave materials. This research used quasi experiment with Pretest and Posttest Control Group Design. Sampling was done by Random Sampling technique. The sample in this study consisted of 2 classes, namely class VIII-4 (Experiment Class) with PBL Learning model assisted by Video and VIII-5 (Control Class) with Conventional learning model. Data collection with tests and documentation. The average data of pretest and posttest learning outcomes in the experimental class were 34.84 and 63.87, respectively, and in the control class 25.06 and 42.96. Data were analyzed with Independent Sample t-test using SPSS Version 21. Based on hypothesis testing, it was found that the PBL learning model assisted by video was effective in using the science literacy skills of students on vibration and wave material in class VIII SMP Negeri 27 Medan in the 2023/2024 academic year. In the experimental class, the achievement of the learning level after being treated with the Video-Assisted PBL model was achieved with an experimental class N-gain value of 45% in the sufficient category. And in the control class using the conventional model, the N-gain obtained was 24% with a very low category.